Practical implications on ergonomic assessments resulting from EN16710-2—ergonomics methods - Marcin Butlewski; Wiktoria Czernecka; Agata Szczepaniak; Marta Pojasek; Marcin Baran (Zeszyty Naukowe Małopolskiej Wyższej Szkoły Ekonomicznej w Tarnowie, 2019)
Ergonomic workplace analysis is a basic element of every ergonomic project. In many cases, however, carried out in a fragmented and unstructured manner it gives an incomplete picture of the assessed work processes. Authors on the basis of their own experience and methodologies contained in EN 16710-2 Ergonomic methods—Part 2: Methodology of work analysis to support design, presented the procedure and the most important elements, the conclusion of which enables reliable ergonomic analysis. The key task in the field of ergonomic analysis is to determine the applicability of the data acquisition apparatus under specific conditions, which can be done by analyzing scientific publications or reports from professional literature. An important element of the report is also evidence that the assessment was carried out by a competent person to whom the Euro-Ergonomist institution can be used, or at least by such a person checked. It should also be ensured that the report contains evidence that a sufficiently large part of the system has been tested. Fragmentary analysis is possible as long as conclusions from it are not extended and areas not covered by it. A very important but often overlooked element of ergonomic analysis is the indication of how the project solved incompatibilities (which are an inherent element of almost every research procedure in the area of production). It allows to determine the validity of the inference based on the collected material, as well as to determine deviations from the applicable standards. The article also presents the method of triangulation as an element of protection against incorrect diagnosis of the method of work implementation.